Production of a rabbit polyclonal anti-elephant IgG antibody for the elephant laboratory investigation - Preeyanat Vongchan (2018)
Blood group phenotyping in elephants is not well researched. Transfusion with incompatible blood may thus result in blood transfusion reactions and may lead to death of the animal. Pathologies resulting from blood incompatibility between the mother and fetus may cause HDN. Several disease investigations also utilized anti-elephant IgG antibody (anti-EIgG) to identify the antibody titer against particular diseases. Of which, reliable and rapid diagnostic tools based on antiglobulin test using anti-EIgG should be developed. This work aimed to purify elephant IgG (EIgG) and produce rabbit anti-EIgG for elephant laboratory investigation. Sera from elephants were pooled and EIgG was purified. Rabbits were immunized weekly with purified EIgG for 8 weeks. Investigation of anti-EIgG rising titer was performed by indirect ELISA. Activity and specificity of rabbit anti-EIgG was determined by EIgG coated red blood cell (RBC) agglutination. Cross-reactivity to other animal IgG was verified by agglutination and indirect ELISA. The results showed that EIgG yield was 21.6 mg/mL serum. Rabbits gradually produced anti-EIgG with a rising titer after first immunization and reached a plateau during week 6-8. Purified rabbit anti-EIgG was demonstrated to specifically agglutinate EIgG coated elephant RBC. Taken together, it could be proposed that the product will be able to serve for elephant blood compatibility testing as well as investigation for other pathologies.